2016
DOI: 10.1007/s11274-015-1979-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on evolutionary relationship of amylases from archaea, bacteria and eukaryota

Abstract: Amylase is one of the earliest characterized enzymes and has many applications in clinical and industrial settings. In biotechnological industries, the amylase activity is enhanced through modifying amylase structure and through cloning and expressing targeted amylases in different species. It is important to understand how engineered amylases can survive from generation to generation. This study used phylogenetic and statistical approaches to explore general patterns of amylases evolution, including 3118 α-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…In addition to this initial gene duplication, some species have experienced further CN increase in both salivary ( AMY1 ) and pancreatic ( AMY2 ) α‐amylase genes. The α‐amylase enzyme exists across the broad taxonomic domains Archaea, Bacteria and Eukarya (Yan & Wu, ) but its expression in saliva has only been recognized in a few mammalian species, with varying levels of expression and diets (see Boehlke et al, ; Chauncey, Henriques, & Tanzer, ; de Sousa‐Pereira et al, ; Junqueira, Toledo, & Doine, ; Young & Schneyer, ). However, to our knowledge, the association of salivary amylase activity with AMY1 CN has only been assessed in humans (Carpenter, Mitchell, & Armour, ; Mandel, Peyrot Des Gachons, Plank, Alarcon, & Breslin, ; Perry et al, ; Tan et al, ; Viljakainen et al, ).…”
Section: Evolution Of Salivary Amylase Amy1 and Amy1 Cnvmentioning
confidence: 99%
“…In addition to this initial gene duplication, some species have experienced further CN increase in both salivary ( AMY1 ) and pancreatic ( AMY2 ) α‐amylase genes. The α‐amylase enzyme exists across the broad taxonomic domains Archaea, Bacteria and Eukarya (Yan & Wu, ) but its expression in saliva has only been recognized in a few mammalian species, with varying levels of expression and diets (see Boehlke et al, ; Chauncey, Henriques, & Tanzer, ; de Sousa‐Pereira et al, ; Junqueira, Toledo, & Doine, ; Young & Schneyer, ). However, to our knowledge, the association of salivary amylase activity with AMY1 CN has only been assessed in humans (Carpenter, Mitchell, & Armour, ; Mandel, Peyrot Des Gachons, Plank, Alarcon, & Breslin, ; Perry et al, ; Tan et al, ; Viljakainen et al, ).…”
Section: Evolution Of Salivary Amylase Amy1 and Amy1 Cnvmentioning
confidence: 99%
“…Alpha-amylases are a large family of endo-glycosyl hydrolases that cleave the internal α,1-4 glycosidic bonds between the glucose units in polysaccharides, such as amylose and amylopectin. They are common in all kingdoms of life and their general properties, three-dimensional structures, and mechanisms of action are extensively reviewed [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The physicochemical parameters of the new alpha-amylases, with low isoelectric point and negative net charge ( Table 3 ) also meet the usual characteristic of haloarchaeal enzymes, as reported by other authors. Yan and Wu [ 43 ] analyzed the sequences of 88 α-amylases from archaea and observed that amylases from haloarchaea have a highly negatively charged surface, and a higher percentage of acidic residues as a mechanism of adaptation to high salinity. Other authors describe similar features for H. hispanica , which has an extracellular amylase with an isoelectric point of 4.2 and a low level of aromatic and hydrophobic residues [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…α‐Amylase is one of the most widespread enzymes in nature. Although all isoforms share a commonality of catalytic function, an enormous range in primary and secondary structures exists (Yan & Wu, ). As such, we consider it highly serendipitous that the AMY2 kit appears to be detecting increased α‐amylase levels associated with PHS and LMA.…”
Section: Discussionmentioning
confidence: 99%